Relationship of D-dimer Value to Mortality in Covid-19 Patients with Acute Coronary Syndrome at Haji Adam Malik Hospital Medan - Putri, Dian Primadia; Sembiring, Rahmad Isnanta; Kembaren, Tambar; Eyanoer, Putri (Journal of Society Medicine, 2023)
Introduction: Coronaviruses (CoVs) are single-stranded positive-sense RNA viruses, which can trigger cardiovascular disease. Inflammation caused by SARS-CoV-2 can affect atherosclerotic plaques, induced prothrombotic changes in the blood and endothelium and caused their instability and myocardial infarction. Several prospective studies have demonstrated an association between increased baseline D-dimer levels and the risk of subsequent cardiovascular events. Several studied had showed the relationship of D-dimer value to mortality in COVID-19 patients with acute coronary syndrome at H. Adam Malik Hospital Medan. Method: This study was a descriptive analytic study using medical record data from central installation patients at H. Adam Malik Hospital in the period August 2020 to August 2021. The sample was calculated using the Lemeshow formula. Then the distribution test was carried out using Shapiro Wilk test. Inferential statistical analysis was performed to assess the relationship of D-dimer to mortality in COVID-19 patients with acute coronary syndrome at H. Adam Malik Hospital Medan using chi-square test. If chi-square criteria were not met, the inferential statistical analysis used was Fisher's exact or other alternative tests. The results were statistically significant if the p value <0.05. Results: 70 subjects participated in the study and the average age of the research subjects was 58.2 years, majority were male. Most subjects experienced severe COVID-19; ECG found ST elevation and comorbid factors were mostly hypertension followed by hypertension and diabetes type 2. There was a relationship between D-dimer value and mortality in COVID-19 patients with acute coronary syndrome, with p value = 0.005. Conclusion: D-dimer values was associated with mortality in COVID-19 patients with acute coronary syndrome.